2009
DOI: 10.4028/www.scientific.net/amr.79-82.907
|View full text |Cite
|
Sign up to set email alerts
|

EBSD Study of Crystallographic Identification on Fe-Al-Si Intermetallic Phases in Aluminide Coatings on Mild Steels

Abstract: Mild steels were coated by hot-dipping in molten aluminum and aluminum-silicon baths at 700 °C for 180 seconds. Phase identification of the Fe-Al or Fe-Al-Si intermetallic compounds in the hot-dipped aluminide steel was carried out by using a combination of scanning electron microscope (SEM), energy dispersive X-ray spectroscopy (EDS), X-ray diffraction (XRD) and electron backscatter diffraction (EBSD). The results showed that the aluminide layer of the hot-dipped aluminum steel possessed a thicker intermetall… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 8 publications
0
6
0
Order By: Relevance
“…One study on the formation of IMC formation with Al-10% Si alloy coating deserves special mention because it involved a short dipping time of 3 seconds [121]. It was observed that a distinct IMC layer of a few micron thicknesses could form at the interface with steel.…”
Section: Studies On Phase Development In the Coating During Solidific...mentioning
confidence: 99%
See 1 more Smart Citation
“…One study on the formation of IMC formation with Al-10% Si alloy coating deserves special mention because it involved a short dipping time of 3 seconds [121]. It was observed that a distinct IMC layer of a few micron thicknesses could form at the interface with steel.…”
Section: Studies On Phase Development In the Coating During Solidific...mentioning
confidence: 99%
“…It can provide crystallographic information regardless of the content of the materials by analyzing generated Kikuchi patterns or electron-backscattered diffraction patterns (EBSPs). Cheng et al reported that the intermetallic layer of the coating consisted of a thin FeAl 3 layer and a thicker Fe 2 Al 5 layer [121]. EBSD provided a rapid phase identification of the ternary compounds based on composition and crystallography.…”
Section: Studies On Phase Development In the Coating During Solidific...mentioning
confidence: 99%
“…In the case of the asreceived steel, for example, the dip-coating process is known to produce a layer of τ 5 at the steel interface. 4,8,10,43,44 This layer acts as a barrier between the Al-Si coating and the Fe in the substrate steel, thereby inhibiting further transformation of the Al-Si coating up to 580 °C. 4,45 Other compounds that have been identified as minority components after the hot-dipping process include τ 1 , τ 6 , η, and θ.…”
Section: ■ Discussionmentioning
confidence: 99%
“…Raman microscopic mapping shows the emergence of intermetallic compounds at temperatures that are consistent with observations in previous studies. In the case of the as-received steel, for example, the dip-coating process is known to produce a layer of τ 5 at the steel interface. ,,,, This layer acts as a barrier between the Al-Si coating and the Fe in the substrate steel, thereby inhibiting further transformation of the Al-Si coating up to 580 °C. , Other compounds that have been identified as minority components after the hot-dipping process include τ 1 , τ 6 , η, and θ. ,,, Previous studies have reported that θ and η form at ca. 650 °C, τ 2 at 830 °C, AlFe at 882 °C, and τ 1 at 900 °C. , AlFe and Al 2 Fe 2 Si emerge at higher temperatures, around 900 °C. , Some EDS and electron back-scattering diffraction measurements suggest that Al-Si-coated steels heated to 900 °C contain mixtures of τ 1 , τ 2 , and ω (FeSi 2 ), while others show τ 1 , τ 5 , AlFe, Al 2 Fe, θ, and η. ,,,, Variations in the composition of the Al-Si-Fe layer may arise due to variations in heating time.…”
Section: Discussionmentioning
confidence: 99%
“…Many researchers from different points of view investigated the morphology and interface characteristics of the coating layer during hot-dip aluminizing techniques [6][7][8][9][10]. Generally, hot-dip aluminizing can be divided into two types, hot dipping in pure aluminum and hot dipping in aluminum alloys, based on the composition of the used molten baths [6].…”
Section: Introductionmentioning
confidence: 99%